Advancing Technology in Healthcare Supply: A Review - Caesar Seta Pandega; Aulia Zikri Rahman (Universitas Pendidikan Indonesia, 2023)
Supply Chain Management (MRP) has an important role in healthcare services, including in Indonesia where the majority of raw materials used by the pharmaceutical industry are imported. From the world perspective, Indonesia's pharmaceutical and healthcare industry is known to be very expensive. The Indonesian government has struggled to control the pharmaceutical industry due to its complexity. Too many players that take roles in this industry are also extending the supply chain flow thereby increasing the price to be paid by the end customer (patient). In this era of globalization, technology has played a role and helped human life in almost all aspects, including the health and pharmaceutical service sectors, therefore it is hoped that the use of advanced technology can be a solution to overcoming the complexity in Indonesian health services.